Eosinophilic Cystitis with Eosinophilic Cholecystitis: A Rare Association. (1st October 2013) - Mallat, F.; Hmida, W.; Mestiri, S.; Ziadi, S.; Sriha, B.; Mokni, M.; Mosbah, F.
Abstract : We describe a rare case of eosinophilic cystitis associated with eosinophilic cholecystitis in a 30-year-old patient who underwent bladder biopsy for irritative voiding symptoms and routine elective cholecystectomy for gallstones. Diagnosis was confirmed by histopathological examination. The rarity of this condition prompted us to report this entity in which no specific cause could be found.